2017
DOI: 10.1016/j.envint.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Particle and bioaerosol characteristics in a paediatric intensive care unit

Abstract: The paediatric intensive care unit (PICU) provides care to critically ill neonates, infants and children. These patients are vulnerable and susceptible to the environment surrounding them, yet there is little information available on indoor air quality and factors affecting it within a PICU. To address this gap in knowledge we conducted continuous indoor and outdoor airborne particle concentration measurements over a two-week period at the Royal Children's Hospital PICU in Brisbane, Australia, and we also coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
(38 reference statements)
1
20
0
2
Order By: Relevance
“…For the protection of HCWs during this COVID-19 pandemic, it is not only essential to recognize which procedures are aerosolizing, but physicians should also [36] Environmental study N/A N/A Air samples in PICU Air samples from rooms in PICU were measured for particle concentration and mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the protection of HCWs during this COVID-19 pandemic, it is not only essential to recognize which procedures are aerosolizing, but physicians should also [36] Environmental study N/A N/A Air samples in PICU Air samples from rooms in PICU were measured for particle concentration and mass.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies revealed that air samples obtained during open endotracheal suctioning in mechanically ventilated patients result in higher concentrations of particulate matter and pathogens like bacteria, viruses and fungi (Table 7) [ [36][37][38][39]. Three retrospective studies, evaluating risk factors for SARS-CoV-1 transmission while providing patient care to SARS patients did not demonstrate that endotracheal suctioning was a significant risk factor for SARS infection [34,40,41].…”
Section: Endotracheal Suctioningmentioning
confidence: 99%
“…Assessing the burden of influenza virus in the air is technically and operationally challenging in real‐world settings such as healthcare institutions . Clinical and environmental studies have utilized a range of instruments to determine the risk of exposure to virus‐laden bioaerosols in health care and agriculture . Limited study sizes underscore the need for consistent approaches across studies in similar settings in order to generate robust comparative data to form clearer conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital patients are particularly vulnerable owing to their health status as evidenced by the rate of nosocomial infections representing a major source of morbidity and mortality worldwide . It is well established that human occupancy and associated activities materially influence the total and biological aerosol burden indoors . One potentially overlooked exposure pathway mediated by humans is exposure to aerosols formerly deposited on clothing and subsequently released to air.…”
Section: Introductionmentioning
confidence: 99%